Environmental Design between heritage and contemporary - Ahmed Talib Hameed Haddad; Kais Abdulhusein Abbas (Iraqi Journal of Architecture and Planning, 2018)
The research aims to demonstrate the importance of the intellectual and technological climate of the era, which is witnessing the development of vocabulary, which is completely different from another time period.  Each generation has its own intellectual and technological specificity. In the context of this intellectual environment will discuss the sustainable climate system affecting the vocabulary of design, and how to achieve the comfort of the human in two different times; the first heritage of the old and the other contemporary. And how we can draw the basic concepts of this system at both times to conclude the different climatic treatments of the Environmental Design between the past and present. The ultimate goal of all this is the comfort of man .The research assumes that there is an important impact of temporal privacy and all that is linked culturally, socially and technologically to the possibility of benefiting from the environmental design treatments available in architecture aimed at achieving human comfort .Therefore, the objective of the research is to confirm this hypothesis through a series of appropriate contextual data. The search results will support the hypothesis .It recommends the adoption of environmental design within the intellectual and technological context of the era. With the need to move away from the environmental solutions of earlier times in the design of the contemporary urban environment because of the difference (intellectual - technological) between them. And replace it by taking advantage of the general principles of heritage solutions at the environmental, intellectual or technological level from a sustainable environmental and climatic perspective.